Relation of diet and income to the docosahexaenoic acid (DHA) level in the breast milk of some Filipino women - Tiangson, Cecile Leah P.; Panlasigui, Leonora N. (2001)
This study was conducted to determine the DHA level in the breast milk of some Filipino women and its relationship to maternal diet and annual income. One hundred lactating women participated. Subject distribution was patterned after the 1997 Family and Income Expenditure Survey regarding the total number of families, total average family income and expenditures by income class in an urban area. The subjects were asked to fill up a 3-day food record to ascertain the nutrient content of their food intake. Hind milk was drawn manually by means of a fabricated glass breast pump and collected in polypropylene vials. These were stored in a freezer maintained at -25°C ± -2°C until subjected to DHA analysis at the University of Montreal. The milk was methylated using the LePage method. The obtained FAMEs were analyzed by GC. Results show that the milk samples contain an average of 188.34 μg DHA per ml of milk while mean %DHA of the milk samples is 0.65% (μg DHA per μg 100 total faty acids in the milk sample). Regression analysis show that average protein intake is a determinant of the DHA level in the milk samples. Further regression of protein intake with annual income shows that it is a significant determinant of protein intake. Thus, income may affect the DHA level indirectly through protein intake. Regression analysis for %DHA shows that health center 1 (Project 4), 2 (UP-Diliman), 3 (Kamuning/New Manila), 5 (Blue Ridge/San Juan) full-time employment, and birthweight are negative determinants of %DHA in milk. Positive determinants of %DHA include attainment of primary and tertiary education.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).-- (UARD-12139T, UARD-12140T).
"March 2001."
Thesis (M. S. Nutrition)--University of the Philippines Diliman.
Keywords: Mothers -- Philippines -- Nutrition; Breast milk; Docosahexaenoic acid; Lactation -- Philippines -- Nutritional aspects